CONJUGATE HEAT TRANSFER WITH VARIABLE FLUID PROPERTIES IN A HORIZONTAL ANNULUS (Sciences & Technology. A, exactes sciences, 2010)
In the present work, we numerically study the three-dimensional conjugate heat transfer in an annular space between two horizontal concentric cylinders; the outer cylinder is subjected to an internal energy generated by Joule effect through its thickness while the inner is adiabatic. The thermal convection in the fluid domain is conjugated to the thermal conduction in the solid. The physical properties of the fluid are thermal dependant. The heat losses from the external outside pipe surface to the surrounding ambient are considered. The model equations of continuity, momenta and energy are numerically solved by a finite volume method with a second order spatiotemporal discretization. The obtained results show the three dimensional aspect of the thermal and dynamical fields with considerable variations of the viscosity and moderate variations of the fluid thermal conductivity. As expected, the mixed convection Nusselt number becomes more superior to that of the forced convection when the Grashof number is increased. At the solid-fluid interface, the results show clearly the azimuthal and axial variations of the local heat flux and the local Nusselt numbers. Following these results, we have tried modelling the average Nusselt number as a function of Richardson number. With the parameters used, the heat transfer is quantified by the correlation:  Nua = 12.8678 Ri (pui 01426)